Answer: q ⇒ p represents the CONVERSE of the original conditional statement.
Step-by-step explanation: Given that p is the hypothesis and q is the conclusion of a conditional statement.
We are to find the representation of q ⇒ p.
We know that
if we interchange the hypothesis and conclusion of a conditional statement, then the new statement is the CONVERSE of the original statement.
In the given conditional statement, since p is the hypothesis and q is the conclusion, so
the statement is p ⇒ q.
So, q ⇒ p is formed by interchanging hypothesis and conclusion.
Thus, q ⇒ p represents the CONVERSE of the original conditional statement.